Design of Agriculture Polymer Waste Processing Instrument - Vovoandwivo Mandatya; Saipul Bahri Daulay; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2015)
It is time for Indonesia to do the right way to overcome the polymer waste problem. So we can make an economic and environmentally friendly way to overcome this problem. Agriculture Polymer Waste Processing Instrument is suitable to overcome the problem nowadays. The purpose of this research was to design, to make, to examine and to analyze the economic value of the Algriculture Polymer Waste Processing Instrument (frying oil polypropilene plastic). This research was done on August-September 2014 at Agriculture Engineering Laboratory, Faculty of Agriculture, University of North Sumatera. Parameters observed were instrument effective capacity, break even point, net present value and internal rate of return. The results showed that this instrument effective capacity was 53,3 ml/hour, the break even point was 60.115,6 ml,  the net present value was 302.518.673,9 rupiah and the internal rate of return was 27,1%. Keywords : distilation, oil, polymer waste